ANALISIS NORMALISASI PENGENDALIAN BANJIR DI SUNGAI BATANG ULAKAN KABUPATEN PADANG PARIAMAN - Syofyan Z (Ensiklopedia of Journal, 2020)
Batang Ulakan is a river located in the Padang Pariaman Regency with a length of 14.35 Km. Batang Ulakan is an area that is prone to flooding, especially in the Sic Cincin area, 2x11 Sic ring sub-district, due to the dense population living on the edge of Batang Ulakan which causes no catchment storage locations. Therefore, the dimensions of Batang Ulakan are planned. In planning the Batang Ulakan dimension, the calculation of the average rainfall uses the Average method of 2 (two) rainfall stations, namely the cage rain station IV and Paraman Talang station. The calculation of the 20 (twenty) annual rainfall plan uses the average of the Normal Distribution method, the Log Normal method, the Log Person III method and the Gumbel method. After that, the conformity test was carried out with Chi Square. In Batang Ulakan River normalization planning through literature studies, data collection, hydrological analysis and hydraulic analysis. The Hasper, Weduwen and Rational methods are used to calculate the planned discharge. From the results of the three methods, the flood discharge used is the Rational method with a return period of 20 years, namely (Q20) 1690.94 m3 / sec. The river cross section is trapezoidal. For the trapezoidal section, the base width is 20 meters, the top width is 38.2 meters with a height of 7.7 meters with a slope of 45 °.